Efficacy safety of chemoprophylactic plasmodium falciparum and sporozoite vaccines for malaria prevention: a systematic review and meta- analysis - I N Kamila, Alya; S Chandrarini, Aqilla; S Devi, Rossi (ACTA Medical Health Sciences, 2025)
PfSPZ-CVac, an innovative vaccine, aims to combat malaria by using live, weakened Plasmodium falciparum sporozoites in combination with chloroquine. This approach employs the whole parasite, triggering a strong immune response and potentially providing long-term protection. The objective of this study is to assess the efficacy and safety of the PfSPZ- Chemoprophylaxis Vaccine (PfSPZ-CVac) for malaria prevention. A systematic review following PRISMA guidelines was conducted, focusing on randomized controlled trials (RCTs) that assessed the efficacy and safety of the vaccine. Seven eligible studies were selected from eight electronic databases. The quality was assessed using the Cochrane Risk of Bias tool, and data analysis was performed using Review Manager 5.4. PfSPZ-CVac combines live sporozoites with chloroquine, which prevents the parasite from entering the liver and enhance the body’s immune response, particularly T-cell activation, to provide long- lasting protection against malaria. The meta-analysis revealed a significant reduction in parasitemia (P<0.00001, I²=35%, MD=0.38). Local solicited adverse events did not show a significant increase (MD=0.73, P=0.45, I²=0%). Similarly, systemic solicited adverse events and unsolicited adverse events demonstrated minimal risks (MD=0.89, P=0.56, I²=23%; MD=0.65, P=0.20, I²=0%). Although PfSPZ-CVac exhibits high efficacy, its administration is complex, and it carries a slight of rare adverse reactions. PfSPZ-CVac demonstrates potential for providing strong, long-term protection against malaria , with a positive safety profile, making it a promising candidate for widespread use in high-transmission regions. DOI : 10.35990/amhs.v3n3.p178-189 REFERENCES World Health Organization. World malaria report 2022 [Internet]. Geneva: WHO; 2022 [cited 2023 Mar 5]. Available from: https://www.who.int/teams/global-malaria-programme/reports/world-malaria-report-2022. World Health Organization. Malaria [Internet]. WHO; 2023 [cited 2023 Mar 5]. Available from: https://www.who.int/news-room/fact-sheets/detail/malaria. Berman J. Chemotherapy against malaria. Br Med Bull. 2000;54(2):459–70. https://doi.org/10.1258/0007142001903250. Cowman AF, Healer J, Marapana D, Marsh K. Malaria: Biology and disease. Cell. 2016;167(3):610–24. https://doi.org/10.1016/j.cell.2016.07.055. RTS,S Clinical Trials Partnership. Efficacy and safety of RTS,S/AS01 malaria vaccine with or without a booster dose in infants and children in Africa: Final results of a phase 3, individually randomised, controlled trial. Lancet. 2015;386(9988):31–45. https://doi.org/10.1016/S0140-6736(15)60721-8. Ghana Health Service. Ghana becomes first country to approve malaria vaccine [Internet]. Accra: GHS; 2023 [cited 2023 Apr 1]. Available from: https://www.ghanahealthservice.org. Laurens MB. RTS,S/AS01 vaccine (Mosquirix™): An overview. Hum Vaccin Immunother. 2020;16(3):480–9. https://doi.org/10.1080/21645515.2019.1669415. World Health Organization. WHO recommends groundbreaking malaria vaccine for children at risk [Internet]. WHO; 2021 [cited 2023 Mar 6]. Available from: https://www.who.int/news/item/06-10-2021-who-recommends-groundbreaking-malaria-vaccine-for-children-at-risk. Programme for Immunization. WHO recommends the R21/Matrix-M malaria vaccine [Internet]. WHO; 2023 [cited 2023 Apr 1]. Available from: https://www.who.int/news/item/02-10-2023-who-recommends-r21-matrix-m-malaria-vaccine. Datoo MS, Natama HM, Somé A, Traoré O, Rouamba T, Bellamy D, et al. Efficacy of a low-dose candidate malaria vaccine, R21 in adjuvant Matrix-M, with seasonal administration to children in Burkina Faso: A randomised controlled trial. Lancet. 2021;397(10287):1809–18. https://doi.org/10.1016/S0140-6736(21)00943-0. gov. Study to evaluate efficacy, immunogenicity and safety of the R21/Matrix-M vaccine (MAL-ED) [Internet]. 2023 [cited 2023 Apr 2]. Available from: https://clinicaltrials.gov/ct2/show/NCT04868604. Mahamar A, Issiaka D, Barry A, Kone DT, Traore F, Sissoko M, et al. Safety and immunogenicity of the R21/Matrix-M malaria vaccine administered seasonally in children in Mali: A randomised, controlled, phase 1/2 trial. Lancet Infect Dis. 2022;22(4):590–8. https://doi.org/10.1016/S1473-3099(21)00559-1. University of Oxford. R21/Matrix-M vaccine shows high-level efficacy of 77% over 12 months of follow-up [Internet]. Oxford; 2022 [cited 2023 Apr 2]. Available from: https://www.ox.ac.uk/news/2022-09-07. R21/Matrix-M malaria vaccine receives WHO recommendation [Internet]. UNICEF; 2023 [cited 2023 Apr 2]. Available from: https://www.unicef.org. World Health Organization. R21/Matrix-M malaria vaccine: WHO recommendation [Internet]. WHO; 2023 [cited 2023 Apr 3]. Available from: https://www.who.int/publications/i/item/9789240072056. Malaria vaccine implementation programme (MVIP) [Internet]. PATH; 2022 [cited 2023 Apr 3]. Available from: https://www.path.org/resources/malaria-vaccine-implementation-programme-mvip. Agnandji ST, Lell B, Fernandes JF, Abossolo BP, Methogo BG, Kabwende AL, et al. A phase 3 trial of RTS,S/AS01 malaria vaccine in African infants. N Engl J Med. 2011;365(20):1863–75. https://doi.org/10.1056/NEJMoa1102287. Otieno L, Akhwale W, Nzila A, Hunt R, Ochola S, Tetteh KKA, et al. Protective efficacy of RTS,S/AS01 malaria vaccine in children 5 to 17 months of age in Kenya and Tanzania: A phase 3, randomized, controlled trial. Lancet Infect Dis. 2016;16(11):1339–48. https://doi.org/10.1016/S1473-3099(16)30227-3. Olotu A, Fegan G, Wambua J, Nyangweso G, Leach A, Lievens M, et al. Seven-year efficacy of RTS,S/AS01 malaria vaccine among young African children. N Engl J Med. 2016;374(26):2519–29. https://doi.org/10.1056/NEJMoa1515257. White MT, Verity R, Griffin JT, Asante KP, Owusu-Agyei S, Greenwood B, et al. Immunogenicity of the RTS,S/AS01 malaria vaccine and implications for duration of vaccine efficacy: Secondary analysis of data from a phase 3 randomised controlled trial. Lancet Infect Dis. 2015;15(12):1450–8. https://doi.org/10.1016/S1473-3099(15)00239-X. Penny MA, Verity R, Bever CA, Galactionova K, Flasche S, White MT, et al. Public health impact and cost-effectiveness of the RTS,S/AS01 malaria vaccine: A systematic comparison of predictions from four mathematical models. Lancet. 2016;387(10016):367–75. https://doi.org/10.1016/S0140-6736(15)00725-4. Ehreth J. The global value of vaccination. Vaccine. 2003;21(7–8):596–600. https://doi.org/10.1016/S0264-410X(02)00623-0. Vaccine investment strategy [Internet]. Gavi, the Vaccine Alliance; 2023 [cited 2023 Apr 3]. Available from: https://www.gavi.org. Advancing the malaria vaccine pipeline [Internet]. PATH; 2022 [cited 2023 Apr 3]. Available from: https://www.path.org/articles/advancing-malaria-vaccine-pipeline. United Nations. Goal 3: Ensure healthy lives and promote well-being for all at all ages [Internet]. UN; 2022 [cited 2023 Apr 3]. Available from: https://sdgs.un.org/goals/goal3. The Global Fund. Malaria and the global fund [Internet]. 2023 [cited 2023 Apr 3]. Available from: https://www.theglobalfund.org/en/malaria. European Medicines Agency. First malaria vaccine receives positive scientific opinion from EMA [Internet]. EMA; 2015 [cited 2023 Apr 4]. Available from: https://www.ema.europa.eu/en/news. UNICEF Supply Division. Vaccine procurement and delivery [Internet]. UNICEF; 2022 [cited 2023 Apr 4]. Available from: https://www.unicef.org/supply. Bill & Melinda Gates Foundation. Malaria strategy overview [Internet]. Gates Foundation; 2023 [cited 2023 Apr 4]. Available from: https://www.gatesfoundation.org. Malaria: Developing better prevention and treatment [Internet]. Wellcome Trust; 2023 [cited 2023 Apr 4]. Available from: https://wellcome.org/what-we-do/our-work/malaria. What is the malaria vaccine pipeline? [Internet]. PATH; 2023 [cited 2023 Apr 4]. Available from: https://www.path.org/articles. RTS,S Clinical Trials Partnership. Long-term safety and efficacy of RTS,S/AS01 malaria vaccine in African infants and children: An open-label 4-year extension study of a phase 3 randomized controlled trial. Lancet Infect Dis. 2021;21(10):1404–16. https://doi.org/10.1016/S1473-3099(20)30779-8. Datoo MS, Natama HM, Somé A, Traoré O, Rouamba T, Bellamy D, et al. Efficacy of the R21/Matrix-M malaria vaccine with seasonal administration in children in Burkina Faso: A double-blind, randomized, controlled trial. Lancet Infect Dis. 2023;23(1):1–10. https://doi.org/10.1016/S1473-3099(22)00541-X. WHO Strategic Advisory Group of Experts on Immunization. WHO SAGE roadmap for prioritizing uses of malaria vaccines [Internet]. WHO; 2022 [cited 2023 Apr 4]. Available from: https://www.who.int/publications. Deeks JJ, Higgins JPT, Altman DG, editors. Chapter 10: Analysing data and undertaking meta-analyses. In: Higgins JPT, Thomas J, Chandler J, Cumpston M, Li T, Page MJ, Welch VA, editors. Cochrane Handbook for Systematic Reviews of Interventions version 6.2 (updated February 2021). Cochrane; 2021. Available from: training.cochrane.org/handbook. Mordmüller B, Surat G, Lagler H, et al. Sterile protection against human malaria by chemoattenuated PfSPZ vaccine. Nature. 2017;542:445–60. https://doi.org/10.1038/nature21060. Camponovo F, Campo JJ, Le TQ, Oberai A, Hung C, Pablo JV, et al. Proteome-wide analysis of a malaria vaccine study reveals personalized humoral immune profiles in Tanzanian adults. eLife. 2020;9:e53080. https://doi.org/10.7554/eLife.53080. Skelly CL, Cassagnol M, Munakomi S. Adverse effects of vaccines. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; 2023 [cited 2023 Apr 4]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK538239/. Ibanez J, Fendel R, Lorenz FR, et al. Efficacy, T cell activation and antibody responses in accelerated Plasmodium falciparum sporozoite chemoprophylaxis vaccine regimens. NPJ Vaccines. 2022;7:59. https://doi.org/10.1038/s41541-022-00473-1. Healy SA, Murphy SC, Hume JCC, Shelton L, Kuntz S, Voorhis WCV, et al. Chemoprophylaxis vaccination: Phase I study to explore stage-specific immunity to Plasmodium falciparum in US adults. Clin Infect Dis. 2020;71(6):1481–90. https://doi.org/10.1093/cid/ciz1010. Mwakingwe-Omari A, Healy SA, Lane J, et al. Two chemoattenuated PfSPZ malaria vaccines induce sterile hepatic immunity. Nature. 2021;595:289–94. https://doi.org/10.1038/s41586-021-03684-z. Sulyok Z, Fendel R, Eder B, et al. Heterologous protection against malaria by a simple chemoattenuated PfSPZ vaccine regimen in a randomized trial. Nat Commun. 2021;12:2518. https://doi.org/10.1038/s41467-021-22740-w. Jongo SA, Urbano V, Church LWP, Olotu A, Manock SR, Schindler T, Mtoro A, et al. Immunogenicity and protective efficacy of radiation-attenuated and chemo-attenuated PfSPZ vaccines in Equatoguinean adults. Am J Trop Med Hyg. 2021;104(1):283–93. https://doi.org/10.4269/ajtmh.20-0435.